Вентильно-индукторный электропривод железнодорожного стрелочного перевода - Петрушин, Александр Дмитриевич; Девликамов, Рашит Музаферович; Шайхиев, Алексей Рифкатович; Васильева, Людмила Михайловна (НТУ "ХПИ", 2010)
The paper is devoted a problem of designing and introduction of the automated electric drive of the railway switch point into base switched reluctance motor.
Switched reluctance drive of the railway switch point
Keywords: электродвигатель бесконтактный; магнит постоянный; ротор